The Protection of Refugees and Stateless Persons: Challenges of International Human Rights Law in an Era of Global Migration Crisis - Kasman Yori Harefa; Supriadi Supriadi; Krisno Hadi Susanto; Ahmad Faisol; Rizal Musa Karim; Nodira Tursunova (Rechtsnormen: Journal of Law, 2026)
Background.The global migration crisis has highlighted major gaps in protecting refugees and stateless persons, as conflict and inequality increase their vulnerability despite existing international human rights frameworks. Purpose. This study examines the effectiveness of international human rights law in addressing the specific protection needs of displaced and stateless populations within modern migration contexts. Method. A qualitative doctrinal and socio-legal approach was used, analyzing international legal instruments, comparative policy frameworks, and secondary data on protection outcomes. Results. While principles like non-refoulement are generally upheld, significant gaps remain in legal recognition and service access, with institutional capacity and international cooperation identified as critical success factors. Conclusion. International law is a necessary but insufficient framework; it requires stronger implementation, better accountability, and more inclusive global approaches to effectively protect vulnerable migrants.